PERADABAN DINASTI ABBASIYAH (Perkembangan Ilmu Pengetahuan) - Muhammad Asra Asra; Moh Abd Azis; Mashuri Rifai (Jurnal Ushuluddin Adab dan Dakwah, 2020)
During the Abbasid empire, Islamic power expanded with its center of government in Baghdad, the expansion of Islamic power and influence moved to the eastern Central Asia, the Indies and the Chinese border. The political stance of the Abasiah daulah is different from that of the Umayyad daulah, the Daulah the Bani Abasiah has more equal power, not only held by the Arabs but is more democratic. The community is divided into two groups, namely a special group and a general group, the general group consists of artists, scholars, fuqoha, poets, merchants, entrepreneurs, workers, and farmers, while the special group consists of caliphs, caliphate families, aristocratic State officials and state officials, in the development of science, the caliphs supported this development, and many foreign language books were translated into Arabic.